2018
DOI: 10.1001/jamadermatol.2018.3435
|View full text |Cite
|
Sign up to set email alerts
|

Lipoid Proteinosis

Abstract: A school-aged boy born of a third-degree consanguineous marriage presented with hoarseness of voice and multiple skincolored papules on the upper eyelids of both eyes present since early childhood. There was no history of neurological complaints or similar history among his family members. Cutaneous examination revealed firm papules set closely together in a beaded fashion on the upper eyelids and lid margins (moniliform blepharosis) of both eyes (Figure). His background skin was waxy, and there were skincolor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…To date, fewer than 500 cases have been documented in the literature. [3][4][5] Homozygous or compound heterozygous mutations in the ECM1 gene located on chromosome 1q21 are believed to be responsible for this condition. 3 The ECM1 gene encodes a glycoprotein that functions as a transporter and binds to growth and differentiation factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, fewer than 500 cases have been documented in the literature. [3][4][5] Homozygous or compound heterozygous mutations in the ECM1 gene located on chromosome 1q21 are believed to be responsible for this condition. 3 The ECM1 gene encodes a glycoprotein that functions as a transporter and binds to growth and differentiation factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hoarseness, caused by infiltration of transparent substances into the vocal cords, is typically the initial clinical manifestation in LP. [4][5][6] Additionally, ocular, laryngeal, and neurological involvement may also occur. 7 The cutaneous manifestations of LP are diverse and often manifest within the first two years of life and present as two overlapping stages.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, review of 51 cases of LP reported in India from 1969 to 2021 is done along with the present case [ Table 1a – c ]. [ 1 4 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] LP is more reported in patients in the age group of 11-20 (51%). More prevalence of LP is reported in males (70.6%).…”
Section: Review and Discussionmentioning
confidence: 99%
“…On review of oral manifestations, 42 cases were found as shown in Table 1c . [ 1 4 5 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 25 26 27 28 29 30 31 32 33 34 35 37 38 39 42 43 44 ] The most common involved site is tongue with typical thick woody appearance followed by restricted tongue movements. In the present case, also similar findings were present.…”
Section: Review and Discussionmentioning
confidence: 99%
“…A skin biopsy can be done to rule out other differentials such as amyloidosis, porphyria, and scleromyxedema. [1] Declaration of patient consent e authors certify that they have obtained all appropriate patient consent.…”
Section: Financial Support and Sponsorshipmentioning
confidence: 99%